The Effect of The Project Based Learning Learning Model in Improving the Gender-Based Science Learning Creativity of Elementary School - Lina Munfarida; Laurens Kaluge; Nawaji Nawaji (BASICA, 2025)
This research was conducted to examine the influence of the Project-Based Learning (PjBL) model on elementary students’ creativity in IPAS learning when viewed from gender differences in Sukun District, Malang City. The study was motivated by the limited development of students’ creativity, which is often associated with the predominance of teacher-centered instructional practices. As a student-oriented approach, PjBL is believed to encourage active participation, creative thinking, and collaborative engagement in IPAS learning. A quantitative method with a quasi-experimental design was applied in this study. The participants were fourth-grade students drawn from three public elementary schools: SDN Sukun 3, SDN Pisangcandi 1, and SDN Mulyorejo 1. Data were gathered using creativity tests and questionnaires. The analysis employed MANOVA after fulfilling the assumptions of normality and homogeneity. The findings demonstrate that: (1) the PjBL model significantly influences students’ creativity in IPAS learning; (2) creativity levels differ between male and female students; and (3) no significant interaction effect was found between the learning model and gender. These results confirm that PjBL effectively enhances creativity while providing equitable learning opportunities for both genders. The study contributes to the development of innovative and gender-responsive IPAS instruction at the elementary level.